Tourism sector decarbonization and policy effectiveness in China: a subsectoral environmental performance analysis - Khan, Asif; Bibi, Sughra; Li, Hanliang; Mu, Dahai (Frontiers in Environmental Science, 2025)
Tourism’s expanding ecological footprint presents a growing governance challenge, particularly in rapidly developing economies such as China, where sectoral growth coincides with ambitious climate targets. This study examines the differentiated environmental and socio-economic impacts of tourism sub-sectors—lodging, entertainment, and food services—under the influence of fiscal and regulatory governance instruments. Using quarterly data from 2000 to 2020 and applying the Autoregressive Distributed Lag (ARDL) approach, we evaluate both short- and long-run dynamics across five key sustainability indicators: greenhouse gas emissions (GHG), air pollutants (PM2.5 and PM10), ecological footprint (ECO-F), and the Human Development Index (HDI). The results reveal strong long-run cointegration among sectoral activities, environmental governance variables, and sustainability outcomes. Lodging exhibits the highest environmental intensity, significantly increasing GHG and ECO-F, while entertainment enhances HDI with moderate ecological trade-offs. Meanwhile, the food sector demonstrates a relatively balanced contribution to sustainability, showing potential in mitigating air pollution. Environmental regulation and taxation show varying effectiveness: regulatory instruments consistently mitigate emissions and improve HDI, whereas fiscal tools yield mixed results depending on sectoral context and energy elasticity. Causality diagnostics uncover complex feedback loops between tourism, energy consumption, and environmental performance, while ECO-F–HDI mapping reveals sector-specific trade-offs between ecological stress and human development gains. The study offers theoretical advancement by integrating tourism-environment analysis with fiscal governance mechanisms and introduces a policy-relevant framework for sustainability calibration at the sub-sectoral level. Findings highlight the need for differentiated, sector-specific governance strategies to align tourism growth with environmental and developmental imperatives, providing empirical evidence to guide low-carbon transitions in tourism economies.